Which factors predict success after discontinuation of inhaled budesonide therapy in children with asthma? - (:unkn) unknown (My University, 2002)
Urinary eosinophil protein X (UEPX) concentration, lung function, and nonspecific bronchial hyperreactivity were determined in 40 asthmatic children (asymptomatic for 6.4 +/- 3.0 months) (mean age 9.8 +/- 2.9 years) receiving inhaled budesonide, in order to establish whether measurement of these parameters is useful in determining discontinuation of inhaled corticosteroid therapy. After the discontinuation of therapy, patients were asked to come to the Outpatient Clinic if symptoms recurred and did not respond to beta2 mimetic usage in 24 hr. Otherwise they were to be seen 2-3 months later for a follow-up visit. UEPX concentration was determined and spirometry was performed on this visit. While UEPX concentrations had increased (p < 0.0001), FEV1, FEF 25-75 and PEF had decreased significantly 2.3 +/- 0.53 months after the cessation of inhaled budesonide therapy in all children (p = 0.004, p = 0.02, p = 0.02, respectively). Due to clinical deterioration, inhaled corticosteroid therapy had to be restarted in 19 (48%) of the children (Group I), while the remaining 21 (52%) (Group II) continued to be asymptomatic during the 2.3 +/- 0.5 months follow-up period. Although the initial UEPX concentrations, spirometer variables, and methacholine PC20 values of these two groups were not statistically different, the duration of clinical remission before discontinuation of budesonide prophylaxis was significantly longer in group II (p = 0.0037). We concluded that, in determining discontinuation of inhaled corticosteroid prophylaxis, duration of clinical remission seems to be a more useful criterion than measurement of UEPX levels, lung function test, and assessment of bronchial hyperreactivity.
Keywords: Female; Humans; Male; Follow-Up Studies; Child; Time Factors; Anti-Inflammatory Agents; Administration, Inhalation; Asthma; Budesonide; Ribonucleases; Bronchial Hyperreactivity; Spirometry; Eosinophil-Derived Neurotoxin